Length-Dependent Modulation of Cytoskeletal Remodeling and Mechanical Energetics in Airway Smooth Muscle - Kim, Hak Rim (American Thoracic Society, 2011)
Actin cytoskeletal remodeling is an important mechanism of airway smooth muscle (ASM) contraction. We tested the hypothesis that mechanical strain modulates the cholinergic receptor–mediated cytoskeletal recruitment of actin-binding and integrin-binding proteins in intact airway smooth muscle, thereby regulating the mechanical energetics of airway smooth muscle. We found that the carbachol-stimulated cytoskeletal recruitment of actin-related protein-3 (Arp3), metavinculin, and talin were up-regulated at short muscle lengths and down-regulated at long muscle lengths, suggesting that the actin cytoskeleton–integrin complex becomes enriched in cross-linked and branched actin filaments in shortened ASM. The mechanical energy output/input ratio during sinusoidal length oscillation was dependent on muscle length, oscillatory amplitude, and cholinergic activation. The enhancing effect of cholinergic stimulation on mechanical energy output/input ratio at short and long muscle lengths may be explained by the length-dependent modulation of cytoskeletal recruitment and crossbridge cycling, respectively. We postulate that ASM functions as a hybrid biomaterial, capable of switching between operating as a cytoskeleton-based mechanical energy store at short muscle lengths to operating as an actomyosin-powered mechanical energy generator at long muscle lengths. This postulate predicts that targeting the signaling molecules involved in cytoskeletal recruitment may provide a novel approach to dilating collapsed airways in obstructive airway disease.